2016
DOI: 10.1073/pnas.1524806113
|View full text |Cite
|
Sign up to set email alerts
|

Engineering titania nanostructure to tune and improve its photocatalytic activity

Abstract: Photocatalytic pathways could prove crucial to the sustainable production of fuels and chemicals required for a carbon-neutral society. Electron−hole recombination is a critical problem that has, so far, limited the efficiency of the most promising photocatalytic materials. Here, we show the efficacy of anisotropy in improving charge separation and thereby boosting the activity of a titania (TiO 2 ) photocatalytic system. Specifically, we show that H 2 production in uniform, one-dimensional brookite titania na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
121
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(130 citation statements)
references
References 52 publications
9
121
0
Order By: Relevance
“…On brookite TiO2 nanorods, reduction and oxidation reactions were observed to proceed predominantly on {210} and {212} The EPR results further indicated that electrons in longer nanorods transfer to Pt faster than electrons in shorter nanorods. The capture of electrons by Pt increases the lifetime of the charge-separated state, as indicated by the much faster decays observed for nanorods without Pt in ethanol [28]. A similar effect was observed for Au surface decoration of brookite nanorods [66], which enabled electrons a lifetime of four orders of magnitude longer due to efficient hopping on brookite lateral facets.…”
Section: Photocatalytic Studiessupporting
confidence: 55%
See 4 more Smart Citations
“…On brookite TiO2 nanorods, reduction and oxidation reactions were observed to proceed predominantly on {210} and {212} The EPR results further indicated that electrons in longer nanorods transfer to Pt faster than electrons in shorter nanorods. The capture of electrons by Pt increases the lifetime of the charge-separated state, as indicated by the much faster decays observed for nanorods without Pt in ethanol [28]. A similar effect was observed for Au surface decoration of brookite nanorods [66], which enabled electrons a lifetime of four orders of magnitude longer due to efficient hopping on brookite lateral facets.…”
Section: Photocatalytic Studiessupporting
confidence: 55%
“…The capture of electrons by Pt increases the lifetime of the chargeseparated state, as indicated by the much faster decays observed for nanorods without Pt in ethanol [28]. A similar effect was observed for Au surface decoration of brookite nanorods [66], which enabled electrons a lifetime of four orders of magnitude longer due to efficient hopping on brookite lateral facets.…”
Section: Photocatalytic Studiessupporting
confidence: 54%
See 3 more Smart Citations